Nitric oxide donor andrographolide enhances humoral and cell-mediated immune responses - Zhang, Bing; Yang, Bo; Du, Lijun; Guo, Yunfen (Cellular and Molecular Biology, 2020)
The present study was aimed to investigate the regulatory effect of Nitric oxide donor andrographolide (Q-1) on cellular immunity in patients with chronic hepatitis B. Peripheral blood mononuclear cells (PBMCs) were isolated from patients with chronic hepatitis B. Cell viability was assessed using 3"‘(4,5"‘dimethyl"‘thiazol"‘2"‘yl)"‘2,5"‘diphenyl"‘2H"‘tetrazolium bromide (MTT) assay. The levels of expression of interferon gamma (IFN-Î³), interleukin 4 (IL-4), interleukin 10 (IL-10) and tumor necrosis factor Î± (TFN-Î±) in PBMCs of patients with chronic hepatitis B were determined using real-time quantitative polymerase chain reaction (qRT-PCR). Anti-HBV effect of isolated HBV DNA was also assessed in vitro. Q-1 had no significant effect on the viability of Vero and isolated PBMCs (p > 0.05). The expression of IFN-Î³ in PBMCs of control patients significantly and time-dependently increased after treatment with Q-1, but the expressions of IL-4 and IL-10 in PBMCs of patients with chronic hepatitis B were decreased significantly and time-dependently (p < 0.05). The function of Th1 cells was significantly enhanced by Q-1 treatment (p < 0.05). The mean replication of HBV DNA in HepG2cells at the three concentrations of Q-1 and adefovir were 3.96 í— 106, 4.13 í— 106 and 4.53 í— 106 copies/mL, respectively. There was no significant difference in the expression of HBV DNA among the concentration levels. These results indicate that andrographolide enhances the function of HBV-specific T cells in patients with chronic hepatitis B.